Human-Human Collaboration in Virtual Teams - Erbe, Heinz-H. (2008)
Extended and networked enterprises distribute the design of products, planning of the production process, and manufacturing regionally if not globally. Employees are therefore confronted with collaborative work over remote sites. A cost effective collaboration depends highly on the organization maintaining a common understanding for this kind of work and a suitable support with information and communication technology. The usual face to face work is going to be replaced at least partly if not totally by computer mediated collaboration. Creating and maintaining virtual teams is a challenge to work conditions as well as technology. New developments on cost-effective connections are providing not only vision and auditory perception but also haptic perception. Research results for improving remote collaboration are presented. Individual, social and cultural aspects are considered as new requirements on the employees of networked and extended enterprises.